2015
DOI: 10.1093/arclin/acv033
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Visuospatial Planning Skills on Adaptive Function Among Young–Adult Survivors of Childhood Brain Tumor

Abstract: The Boston Qualitative Scoring System (BQSS) was used as a method to examine executive skills on the Rey-Osterrieth complex figure (ROCF). Young-adult survivors of childhood brain tumor (N = 31) and a demographically-matched comparison group (N = 33) completed the ROCF copy version and Grooved Pegboard, and informants were administered the Scales of Independent Behavior-Revised (SIB-R) and Behavior Rating Inventory of Executive Function (BRIEF). Survivors had significantly lower BQSS planning and SIB-R communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Six articles reported impaired daily functioning and/or functional living skills, survivor restrictions ranged widely in severity, with only a small minority reporting no limitation in daily activities . Qualitative work linked these restrictions to impaired cognitive functioning through difficulties with reading or handling finances, or managing medications .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six articles reported impaired daily functioning and/or functional living skills, survivor restrictions ranged widely in severity, with only a small minority reporting no limitation in daily activities . Qualitative work linked these restrictions to impaired cognitive functioning through difficulties with reading or handling finances, or managing medications .…”
Section: Resultsmentioning
confidence: 99%
“…Attentional deficits were particularly challenging because of their consequent impact on the development of other cognitive abilities, social functioning, and academic achievement . Evidence suggested that AYA survivors scored lower in Intelligence Quotient (IQ) scores and had limited mathematical skills . AYAs scored lower in IQ testing than population controls.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations